Air Quality Monitoring System Based Internet Of Things - arkhan, muhammad ghozi; Elsi, Zulhipni Reno Saputra (Brilliance: Research of Artificial Intelligence, 2024)
This research aims to develop an Internet of Things (IoT)-based air quality monitoring system using the ESP8266 module along with DHT11 and MQ135 sensors. The system is designed to monitor temperature, humidity, and the concentration of harmful gases in the air, with real-time results accessible through the Blynk application on Android devices. The DHT11 sensor measures temperature and humidity, while the MQ135 sensor detects air quality based on concentrations of harmful gases such as carbon dioxide (CO2) and ammonia. Data from these sensors is transmitted to an IoT platform for real-time display. The research methodology follows a prototype model, starting with planning, system modeling, hardware development, and finally, system testing. During testing, the DHT11 and MQ135 sensors demonstrated accuracy in measuring temperature, humidity, and pollutant levels. Results show that the system functions as expected, with sensors responsive to environmental changes such as increases in temperature or pollutant levels. Additionally, the Blynk platform allows users to monitor air quality remotely and receive notifications if air quality reaches hazardous levels. This system is expected to be applicable in environments that require continuous air quality monitoring, such as hospitals, offices, or other enclosed spaces. The study’s findings indicate that this IoT-based air quality monitoring system effectively detects rapid changes in air quality, contributing to environmental health efforts and raising public awareness about the importance of clean air.